2001
DOI: 10.1007/s002470100533
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous image-guided needle biopsy in children - summary of our experience with 57 children

Abstract: Percutaneous image-guided needle biopsy is a simple, minimally invasive, safe and accurate method for the evaluation of children with suspicious masses. These data suggest that image-guided needle biopsy is an excellent tool for diagnosing solid tumors in the pediatric population. Negative studies should be considered nondiagnostic and followed by excisional surgical biopsies when clinical suspicion of malignancy is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 0 publications
2
28
0
2
Order By: Relevance
“…Furthermore, we did not observe any increased morbidity associated with taking multiple cores (15)(16)(17)(18)(19)(20) as opposed to few core samples (3)(4)(5) to ensure adequate diagnosis and adequate tissue for cytogenetic studies and for enrollment into Children's Oncology Group clinical trials. In addition, needle core biopsy may be advantageous in diagnosing metastatic tumors in patients with known neuroblastoma.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, we did not observe any increased morbidity associated with taking multiple cores (15)(16)(17)(18)(19)(20) as opposed to few core samples (3)(4)(5) to ensure adequate diagnosis and adequate tissue for cytogenetic studies and for enrollment into Children's Oncology Group clinical trials. In addition, needle core biopsy may be advantageous in diagnosing metastatic tumors in patients with known neuroblastoma.…”
Section: Discussionmentioning
confidence: 87%
“…Open surgical biopsy may have higher risks than needle biopsy with increased risk of intraoperative and postoperative hemorrhage, increased morbidity, delay in initiating chemotherapy, and risks related to open surgical procedures in general [6,7,[13][14][15]. On the other hand, the primary criticism of needle core biopsies has been the possibility of inadequate tissue sampling, which can delay diagnosis and subsequent treatment.…”
Section: Discussionmentioning
confidence: 95%
“…However, percutaneous imaging biopsies will be used frequently for tissue diagnostics of pediatric neoplastic and inflammatory processes [28,29]. The published data suggest that image-guided needle biopsy is an excellent tool for diagnosing solid tumors in the pediatric population, although these authors used only CT for the guidance of the biopsies [28][29][30].…”
Section: Discussionmentioning
confidence: 98%
“…However, only a few studies have been undertaken to evaluate the potential of CT-guided TLB in the paediatric age group. Some authors have shown that CT-guided TLB can help diagnose recurrence or metastasis in children with known or suspected intrathoracic tumours [22][23][24]. In inflammatory pulmonary disease CT guidance can be a helpful tool to drain abscesses or infected congenital lesions even in infants and newborns; CT guidance is used to either aspirate infected fluid or to place a drain within an abscess [21,25,26].…”
Section: Discussionmentioning
confidence: 99%